The fourth sector in Portugal - Pires de Almeida, Filipa; Zózimo, Ricardo; Azevedo, Carlos (IE University, 2020)
The Portuguese impact ecosystem has seen tremendous growth in the last decade. From a system that was mostly underpinned by charitable organizations, it has evolved to one that creates and diffuses innovation, is host to multiple organizations and pilot initiatives and has permeated the actions and policies of central and local governments. This has been achieved by focusing on three key dimensions: human capital, policy and funding. This report begins by focusing on human capital and how a small but interconnected number of private and public players achieved this transformational change in a very short period of time. In demonstrating the role of cooperation, it underlines how the ecosystem grew by players building something that was bigger than their own individual contributions. Our initial historical overview of the development of human capital will also underline what types of players were key to this growth.
Keywords: Fourth Sector; Cuarto sector; Economy; Economía; Europe; Europa; Portugal